1996
DOI: 10.1111/j.1744-6155.1996.tb00015.x
|View full text |Cite
|
Sign up to set email alerts
|

Children, Coping, and the Stress of Illness: A Synthesis of the Research

Abstract: purpose. To synthesize and critique the current research on coping strategies used by children who are ill, to identify gaps in the research base, and to provide direction for practice, future research, and theory development population. 32 research articles on coping strategies used by children with chronic or acute illness conclusions. Children's repertoire of coping strategies is the same during health and illness, although the frequency or effectiveness of some of the strategies is often different. prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
0
11
0
1
Order By: Relevance
“…In addition, the type of strategies that children use to cope with disease, hospitalization, and surgery might be relevant to predict children's worries about surgery. Coping is defined as the set of strategies people use to adapt to stressful situations [35,36] and adverse events [12,37]. The efficacy of preoperative preparation programs could be affected by the individual coping strategies [38].…”
mentioning
confidence: 99%
“…In addition, the type of strategies that children use to cope with disease, hospitalization, and surgery might be relevant to predict children's worries about surgery. Coping is defined as the set of strategies people use to adapt to stressful situations [35,36] and adverse events [12,37]. The efficacy of preoperative preparation programs could be affected by the individual coping strategies [38].…”
mentioning
confidence: 99%
“…A review by Capurso and Pazzagli (2015) showed that out of 40 studies on coping in children, play was either disregarded or only considered as an avoidant or distracting activity. Additionally, a search for “play” in some of the most recent reviews and theoretical papers on coping and child development (i.e., Ryan-Wenger, 1992, 1996; Fields and Prinz, 1997; Losoya et al, 1998; Compas et al, 2001; Zimmer-Gembeck and Skinner, 2011, 2016), has not revealed any meaningful discussion of the term. Play is often not mentioned, or when it is, is only seen as an attempt by the child to distance themselves from the stressor or delay the need to face the situation.…”
Section: Copingmentioning
confidence: 99%
“…Because there is a positive relationship between reaction to disease and consequences of the illness, it should be beneficial when coping behavior is more adaptive in nature (Wenger 1996). Coping can be described as the cognitive and behavioral strategies that individuals use to deal with different dimensions of stress (Folkman, 2001).…”
Section: Introductionmentioning
confidence: 99%